Readability Level Analysis and the Usage of Complex Words on Grade 8 Students’ Argumentative Essay - Lisana Rahmati Marzan (Mitra Palupi, 2022)
Background: Writing as medium of communications has become the pivotal accomplishments of language learning objectives. It still becomes the challenging part especially for learners who come from non-English speaking country. Their hindrances to elaborate the sentences, lack vocabularies and use the right words in their essay make the essay difficult to understand. Purpose: Therefore, the significance of the research is to identify the readability level of student’s essay written by grade eight learners under Cambridge curriculum. Design and methods: This readability is to define which level of readers is suitable to read the text and who will understand it. Then, one of the elements in analyzing the level of readability is the number of complex words the texts. Therefore, there are about 13 students’ essays were examined using Flesh-Kincaid Ease Formula and SMOG index. Results: The result found out the they have diverse readability level in between 7th grade to college level. By these results as well, it appears the number of complex words used in their essay which then being described of what kinds of complex sentences used in their essays.